Evaluasi dan Penilaian Usaha X Melalui Business Model Canvas - Verda Jesikasari; Dewi Fadila; Marieska Lupikawaty (Jurnal Bisnis Kreatif dan Inovatif, 2025)
SQ Florist has been a flower board-making service provider since 2019. Currently, SQ Florist faces several obstacles, including ineffective social media promotions, limited staff training in digital marketing, and a suboptimal flower board production process. Furthermore, revenue recording is still manual, resulting in inefficient financial management. This study aims to expand market reach while improving service quality so that SQ Florist can compete better. The research method used is a qualitative approach with data collection techniques through observation, interviews, documentation, and literature studies. The analysis tool uses the Business Model Canvas, which describes nine business elements including customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures. The analysis results show that SQ Florist's business model is generally quite good, although there are areas for improvement, particularly in building relationships with customers, digital marketing, and product innovation. The use of social media such as Instagram and TikTok must be optimized by presenting promotional content in the form of attractive photos and videos to make online marketing more effective. Additionally, improving supplier relationships and offering differentiated products, such as flower bouquets or cash, can increase customer value. To facilitate decision-making, it is recommended to improve financial record-keeping through the use of digital applications. This step is expected to enable SQ Florist to improve its business sustainability, open more market opportunities, and compete more competitively in the creative services industry. By improving each element of the BMC, it is hoped that business sustainability and competitiveness can be further enhanced.